Measuring the Online Shopping Trends and Their Effects on Consumer buying Habits in Iraqi Kurdistan During the Covid-19 Pandemic - Sardar Hassan Khal Hamza; Jawad Mohammedameen Issa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This paper assesses the level of online shopping trends in Iraqi Kurdistan during the Covid-19 pandemic. To understand the level of online shopping trends and their effects on buying habits, a deep discussion was built on previous studies. The quantitative research method was used for this research. Through Google Forms, a unified self-response survey questionnaire was distributed online and data were directly collected and translated into statistical numbers. SPSS was used to measure the reliability and validity of the items. Due to the Coronavirus movement restriction, a Convenient sampling method was best to reach the research population. Thus, online shopping trends were measured and their effects on customer buying behavior were predicted through the participant’s regression analysis. The findings suggest online shopping is increasing in popularity. Also, young people are not only keen to shop more online but set up their e-businesses while taking advantage of social media sites, which can be used to target their own micro-online communities that do not go beyond geographical borders. To accelerate this trend many believe the government needs to work on better banking and legal system. This research provides some hard data that need to be investigated more on how to manage and make the online experience safer